2006
DOI: 10.1128/mcb.01453-06
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is Activated for Cell Survival after Endoplasmic ReticulumStress

Abstract: Eukaryotic cells deal with accumulation of unfolded proteins in the endoplasmic reticulum (ER) by the unfolded protein response, involving the induction of molecular chaperones, translational attenuation, and ER-associated degradation, to prevent cell death. Here, we found that the autophagy system is activated as a novel signaling pathway in response to ER stress. Treatment of SK-N-SH neuroblastoma cells with ER stressors markedly induced the formation of autophagosomes, which were recognized at the ultrastru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

74
1,428
4
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,652 publications
(1,519 citation statements)
references
References 49 publications
74
1,428
4
13
Order By: Relevance
“…When treated with ER stress, atg5 À/À cells died faster than atg5 þ / þ cells (Supplementary Figure S5D), consistent with recent reports that autophagy acts as a survival mechanism to suppress apoptosis in response to ER stress. 16,17 As anticipated, Bcl-xL protected both atg5 þ / þ and atg5 À/À cells from acute apoptosis. In response to prolonged ER stress the Bcl-xLoverexpressing cells progressively died.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…When treated with ER stress, atg5 À/À cells died faster than atg5 þ / þ cells (Supplementary Figure S5D), consistent with recent reports that autophagy acts as a survival mechanism to suppress apoptosis in response to ER stress. 16,17 As anticipated, Bcl-xL protected both atg5 þ / þ and atg5 À/À cells from acute apoptosis. In response to prolonged ER stress the Bcl-xLoverexpressing cells progressively died.…”
supporting
confidence: 71%
“…[16][17][18][19] In contrast, in apoptosis-deficient cells prolonged autophagy provokes cell death, and its absence imparts protection. This may be because in these cells where excessive ER stress fails to induce apoptosis, the stressing situation keeps accumulating to a point where autophagy is massively induced subsequently leading to cell damage and necrosis.…”
mentioning
confidence: 99%
“…Studies reported that ER stress led to autophagy [30][31][32] and that RINT1 was associated with autophagy. 21 Therefore, we decided to monitor autophagy in Rint1-deficient cortices.…”
Section: Resultsmentioning
confidence: 99%
“…These vesicles, termed autophagosomes, then fuse to lysosomes, forming autolysosomes, which break down the contents of the vesicle (Figure 1.4). Autophagy can be induced under a range of situations and stimuli, including growth factor withdrawal 114 , inhibition of degradation by the ubiquitin-proteasome system 115 , increases in cytosolic calcium 116 and endoplasmic reticulum stress 117 . Morphologically, autophagy can be identified by electron microscopy where cytoplasmic vacuolation without chromatin condensation is observed.…”
Section: Autophagymentioning
confidence: 99%